A review of Encapsulated liquid smoke. Issue 1 (April 2020) - Andy,; Abustam, E; Malaka, R; Purwanti, S
Abstract: Liquid smoke is the condensation result of wood pyrolysis. It contains lots of compounds formed by constituent pyrolysis process such as cellulose, hemicellulose and lignin. Lignin can be used to produce organic acids, phenols, carbonyl that become the compound of natural antibiotics, antioxidants, antibiotic, disinfectants, or as biopesticides and food preservation. Those compounds have different proportions such as type, wood moisture and pyrolysis temperature. Liquid smoke from wood can be used as natural antibiotics contains compounds that can be extracted such as phenol derivatives, which can inhibit microbes' growth. There are many studies about raw materials of liquid smoke such as: rice husk, coconut shell, Meranti sawdust, corncob and cinnamon. Based on literature study, Liquid smoke from coconut shell has percentage phenol 2.24%, total acid 15.7% highest than other material. Followed by the lowest pH 1.41. It can be concluded liquid smoke from coconut shell can be used natural antibiotics in animals. Coconut shell liquid smoke as a natural antibiotic has limitation in distribution and susceptible to physical and chemical changes during storage. Therefore, it was necessary to developed encapsulation of coconut shell liquid smoke. The functional properties of liquid smoke microcapsules can be maintained by using chitosan and maltodextrin as encapsulant. The aims of this review are to understand coconut shell as the best raw material of liquid smoke, after being encapsulated that can be used as natural antibiotics in animals. Based on literature study, coconut shell liquid smoke encapsulated using maltodextrin-chitosan has pH (2.70 ± 0.08), total acid (2.70 ± 0.08%) and total phenol (4.40 ± 0.05%). The paper stresses the need for more studies on using of liquid smoke encapsulated of coconut shell as natural antibiotics in animals.